Karakteristik Kepemimpinan di PT. Priyant Anugerah Mining Kabupaten Paser - Islamiah, Farida; Baihaqi, Ahmad (JUSIE (Jurnal Sosial dan Ilmu Ekonomi), 2017)
Leadership is influence the activities of people to want to work together to achieve goals. The character of a very influential leader to achieve organizational goals. The character of a leader is the ability of management, need for achievement, intelligence, assertiveness, confidence and initiative. This study aims to determine the dominant character of the PT leadership. Priyant Anugerah Mining Paser. The samples used were 82 employees. Data were analyzed using Confirmatory Factor Analysis (CFA). Based on the results of the analysis, it was concluded that the most dominant character of the leader is able to carry out management functions by 85.93% and less dominant leader's character that led initiative in providing solutions to the problems that occur in the company amounted to 29.48%.